Processes of pedagogical differentiation: perspectives of the students of the initial formation and of teachers of the 1st CBE - Duarte, Vanessa (2020)
Dealing with the diversity of students in today's classrooms is a challenge teachers face. Indeed, to believe that equal teaching for all can be advantageous is an illusion. It is precisely in this context that pedagogical differentiation appears as a response that allows the teacher to promote equal opportunities for all students. The study that we propose to present is developed within the scope of this problem, under the theme "Processes of pedagogical differentiation: perspectives of students of initial formation and teachers of the Basic Education". The purpose of the research is to analyze the conceptions and practices of teachers of Basic Education and students of initial teacher formation on the process of pedagogical differentiation. The following specific objectives are identified: (i) characterize the conceptions of students of the initial formation and teachers of Basic Education on the processes of pedagogical differentiation; (ii) identify the practices of pedagogical differentiation enunciated by teachers; (iii) compare the conceptions of students (future teachers) and teachers about the processes of pedagogical differentiation and (iv) compare the teachers' conceptions about the processes of pedagogical differentiation with the practices they enunciate. For this purpose, a quantitative methodology was used. Thirty-one students from the initial teacher formation courses and 51 teachers from Basic Education participated in the study. For the data collection, the questionnaire survey was used. Data processing was carried out using the Statistical Package for Social Sciences (SPSS) software. The results of the study made it possible to show that the students of the initial formation have conceptions closer to the theoretical references than the professors in exercise. For their part, teachers who show greater agreement with the appropriate conceptions about processes of pedagogical differentiation, also refer to the use of pedagogical practices of differentiation with their students.